MAGMA MINGLING AS INDICATED BY TEXTURE AND SR / BA RATIOS OF PLAGIOCLASE PHENOCRYSTS FROM UNZEN VOLCANO, SW JAPAN - Browne B.L.; Eichelberger J.C.; Patino L.C.; Vogel T.A.; Uto K.; Hoshizumi H. (My University, 2006)
Textural and geochemical characteristics of plagioclase phenocrysts from the eruptive products of Mount Unzen (SW Japan) record repeated intrusions of basaltic magma into a dacitic host magma chamber over the lifetime of the volcano. An important aspect of this mixing style is the exchange of phenocrysts between the intruding basalt magma and host dacite magma, and the effect that this wide-reaching mixing style has on the mineralogical diversity of the erupted products. Plagioclase phenocrysts that originally crystallized from the host dacite magma are identified by oscillatory zoning patterns, low An content cores (An45 to An60), and low Sr / Ba ratios. Host-derived plagioclase phenocrysts are engulfed during intrusion of basaltic magma, evidenced by their presence in basaltic to andesitic enclaves. In response to changes in temperature and composition of the surrounding melt, the engulfed plagioclases develop resorption zones, which are composed of a densely packed network of micron-sized glass inclusions and high An content plagioclase (An72-An92) with high Sr / Ba ratios that match those of plagioclase microphenocrysts inherent to the enclave-forming magma. Over time, host-derived plagioclase phenocrysts that were once engulfed during replenishment events are recycled back to the host as enclaves disaggregate (e.g.[ Clynne, M.A., 1989. The disaggregation of quenched magmatic inclusions contributes to chemical diversity in silicic lavas of Lassen Peak, California. Bull New Mexico Bureau of Mines and Mineral Resources, 131: 54]). An eruption of andesite lava with no enclaves, something particularly unique for Unzen, occurred in 1663. Similar to enclaves, all plagioclase phenocrysts in this lava flow are surrounded by resorption zones suggesting that the 1663 lava may represent a magma that was erupted after thoroughly mixing with the intruding basaltic. Using experimentally calibrated crystallization rates, we estimate that phenocrysts exist in the Unzen chamber a minimum of 0.5-3 months between the time of their encounter with a basaltic intrusion and eruption. © 2006 Elsevier B.V. All rights reserved.
Keywords: ENCLAVES; LASER ABLATION ICP-MS; MAGMA MIXING; PLAGIOCLASE; TRACE ELEMENTS; UNZEN VOLCANO